Pengaruh Latihan Menggunakan Belt Training dan Bendel Kaki Terhadap Peningkatan Passing Pada Siswa Ekstrakurikuler Futsal SMA Negeri 6 Palopo - Rahmat Rais; Saman, Saman; Riswanto, A Heri; Hidayat, Rachmat (Universitas Hamzanwadi, 2025)
The main problem in this study was the low quality of passing, particularly in terms of strength and speed, among futsal extracurricular students at SMAN 6 Palopo. This study aims to analyze the effect of training using belt training and ankle weights on improving passing skills. The method used is an experiment with a pretest-posttest two-group design. A total of 30 students were divided into two groups: Group A was given training using belt training and Group B used ankle weights for 16 sessions. Passing ability was measured using a 30-second wall passing test. Data analysis showed that both groups experienced a significant improvement in passing after the treatment, based on the paired sample t-test (p < 0.05). However, the independent sample t-test proved that there was a significant difference between the two groups (p = 0.000). The belt training group showed a greater average improvement (from 13.07 to 19.33) than the ankle band group (from 12.80 to 16.20). The conclusion of this study is that although both are effective, training using belt training proved to be statistically more effective than ankle bands in improving students' futsal passing skills.